Impact of HIV infection on consolidative radiotherapy for non-Hodgkin diffuse large B-cell lymphoma - Carolina Trindade Mello Medici; Geovanne Pedro Mauro; Lucas Coelho Casimiro; Eduardo Weltman (Radiation Oncology, 2020)
Abstract Objectives Even though frequent, it is not known how HIV infection and treatment impact in the consolidation by radiotherapy of non-Hodgkin diffuse large B-cell lymphomas (DBCL). This article aim to assess that difference that HIV makes on radiation treatment. Patients and methods A retrospective cohort of all DBCL patients treated with chemotherapy and consolidative radiotherapy at a single institution between 2010 and 2018 was assessed. All patients had biopsy-proven lymphoma and were included if radiation was part of the treatment and had at least 6 months of follow-up or were followed until death. Results Three-hundred fifty-nine (359) patients were selected, with a median age at diagnosis of 57.7 years (13–90 years). Twenty-eight patients (7.8%) were HIV positive. Median follow-up was 48.0 months. Female patients were 51.3% and most had a good performance in the ECOG scale (78.8% are ECOG 0–1). Median overall survival was not reached, but mean OS was 50.1 months with 86 deaths. Median progression-free survival was 48.7 months. HIV infection had no impact on OS (p = 0.580) or PFS (p = 0.347) among patients treated with RT. HIV positive patients were more frequently staged only with CT (p > 0.05) with no impact on PFS (p = 0.191). No HIV positive patient received rituximab due to local policy restrictions and HIV positive patients were more prone to receive CHOP-like chemotherapy (p < 0.05), specially ones with etoposide (CHOEP). CHOP was associated with better survival (p = 0.015) in the overall population and in the HIV negative population (p = 0.002), but not in the HIV positive population (p = 0.982). RT toxicities were not overall more frequent in the HIV positive population (p = 0.567), except for fatigue (p < 0.05) and hematological toxicities (p = 0.022). Conclusion HIV status did not influence on survival when patients were treated with consolidative radiotherapy. HIV infection was a bias on our sample for staging methods and chemotherapy regimens choices. For HIV positive patients there was an increase in fatigue and hematological toxicities of any grade with radiation.